FUZZY TOPOLOGICAL MODULES INDUCED BY FUZZY PSEUDO NORMED MODULE - Mohammed Melgat, Dr. Basim (Journal of Advance Research in Mathematics and Statistics (ISSN 2208-2409), 2023)
In this article, we give defines about fuzzy pseudo norm module space and fuzzy metric module space which induces by this space. Complete metric space was proved. Also we are defining fuzzy topological module space which induces by fuzzy metric module space.